2014
DOI: 10.1186/1471-2431-14-271
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obesity in children with congenital heart disease: combination of risks for the future?

Abstract: BackgroundChildren who have unhealthy lifestyles are predisposed to develop hypertension, dyslipidemia and other complications. The epidemic of obesity is also affecting children with congenital heart disease. The aim of this study is to estimate the prevalence of obesity and describe associated risk factors, including family history in children with congenital heart disease.MethodsA cross-sectional study with 316 children and adolescents with congenital heart disease seen in an outpatient clinic of a referenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
44
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 30 publications
(39 reference statements)
8
44
0
1
Order By: Relevance
“…These modifiable risk factors have been well discussed in the literature on children without heart disease. 22 Vitamin E, which in this study was associated with the classification of BMI, is a fat-soluble antioxidant that occurs naturally. This micronutrient has been proposed for the prevention and protection of cardiovascular events.…”
Section: Discussionmentioning
confidence: 90%
“…These modifiable risk factors have been well discussed in the literature on children without heart disease. 22 Vitamin E, which in this study was associated with the classification of BMI, is a fat-soluble antioxidant that occurs naturally. This micronutrient has been proposed for the prevention and protection of cardiovascular events.…”
Section: Discussionmentioning
confidence: 90%
“…In a cross‐sectional study, Moons and colleagues collected data on 1976 adults with CHD (median age 26 years) and demonstrated a higher rate of hypertension, obesity, and T2DM relative to the national population, with only 20% of subjects with CHD abiding by a “heart‐healthy” lifestyle. Barbiero and colleagues demonstrated in 316 CHD outpatients a rate of dyslipidemia, excess weight, and family history of T2DM that equaled the rate of the general population and called for additional attention to the aim for healthy cardiovascular behaviors in the CHD community.…”
Section: Discussionmentioning
confidence: 99%
“…While obesity is a clearly described risk factor for T2DM, we are not able to determine to what extent the elevated rate of DM after age 30 in the CHD population is driven by body habitus. However, we can draw from previous literature on the rate of overweight/obesity in the CHD population from 2 large American centers, as well as data from Belgium and Brazil, that demonstrate a rate of overweight and obesity that is not substantially worse in CHD survivors relative to their general population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies have consistently reported that adults with CHD present with modifiable risk factors at rates that warrant attention . While it is well established that cardiovascular risk factors track from childhood to adulthood in the general population, data on modifiable risk factor prevalence in youth with CHD are scarce, and largely focused on the troubling prevalence of overweight and obesity in these children …”
Section: Introductionmentioning
confidence: 99%